Relationship between vitamin D status and left ventricular geometry in a healthy population: results from the Baltimore Longitudinal Study of Aging. (12th November 2012) - Ameri, P.; Canepa, M.; Milaneschi, Y.; Spallarossa, P.; Leoncini, G.; Giallauria, F.; Strait, J. B.; Lakatta, E. G.; Brunelli, C.; Murialdo, G.; Ferrucci, L.
Abstract Objectives The effects of vitamin D on the heart have been studied in patients with cardiac disease, but not in healthy persons. We investigated the relation between vitamin D status and left ventricular (LV) structure and function in community‐dwelling subjects without heart disease. Design The relationship between concentrations of 25‐hydroxyvitamin D [25(OH)D], a marker of vitamin D reserve, and LV transthoracic echocardiography measures was analysed in 711 participants in the Baltimore Longitudinal Study of Aging who were without cardiac disease. Results Mean 25(OH)D in the study population was 32.3 ± 11.4 ng mL−1; only 15.5% of subjects had moderate or severe vitamin D deficiency [25(OH)D < 20 ng mL−1]. Adjusting for age, body mass index, cardiovascular disease risk factors, physical activity, calcium and parathyroid hormone, 25(OH)D was positively correlated with LV thickness (β 0.095, SE 0.039, P < 0.05) and LV mass index (β 7.5, SE 2.6, P < 0.01). A significant nonlinear relation between 25(OH)D and LV concentric remodelling was observed. LV remodelling was more likely in participants with 25(OH)D levels <30 ng mL−1 [odds ratio (OR) 1.24; 95% confidence interval (CI) 0.83–1.85] or ≥38 ng mL−1 (OR 1.73; 95% CI 1.13–2.65), compared with those with 30–37 ng mL−1 25(OH)D. Consistently, LV relative wall thickness was significantly lower (P for trend=0.05), and LV diastolic internal diameter index (P for trend<0.05) and end‐diastolic volume index (P for trend<0.05) were significantly higher in subjects with 30–37 ng mL−1 25(OH)D compared to the rest of the study population. There was a significant interaction between 25(OH)D and hypertension on the risk of LV hypertrophy (P < 0.05). Conclusions In a population‐based sample of predominantly vitamin D‐sufficient subjects without heart disease, LV geometry was most favourable at intermediate 25(OH)D concentrations.